Rediseño de un banco de bombas periféricas para pruebas de conexión en serie, paralelo y mixto para el laboratorio de fluidos de la Universidad Antonio Nariño (2023)
The purpose of the following work is the construction and redesign of an existing test bench for centrifugal pumps at the Antonio Nariño University of Tunja, which would provide a great help for mechanical engineering students, mainly at the time of consolidating the knowledge acquired theoretically in different subjects related to fluid mechanics and hydraulic machines, putting them into practice on an experimental basis; In this way, to know the advantages that can be obtained and applied when two or more pumps are connected in series, parallel and mixed, since this type of connection provides better capabilities and to be able to provide the student with the ability to choose the system that best suits when making a connection of this type in the industry or in professional life.